Early clinical and radiological outcomes of cases undergoing cementless total hip arthroplasty: Early clinical outcomes of total hip arthroplasty - Yazici Ali̇kemal; Ardıçoğlu, Kemalettin (Journal of Surgery and Medicine, 2026)
Background/Aim: Cementless total hip arthroplasty was developed to eliminate the disadvantages of cemented systems and to provide long-term biological fixation. It is widely used in the treatment of advanced coxarthrosis. This study aimed to evaluate early clinical and radiological outcomes of patients who underwent cementless primary total hip arthroplasty (THA) for different etiological reasons and to discuss the findings in light of the literature. Methods: This retrospective study evaluated 56 hips of 53 patients who underwent cementless primary THA and had regular clinical and radiological follow-up between August 1991 and November 1995. The mean follow-up duration was 16.9 months. Clinical evaluation was performed using the Modified Harris Hip Score (mHHS). Radiological evaluations were performed according to the criteria recommended by the American Hip Society for cementless prostheses. Heterotopic ossification (HO) was assessed using the Brooker classification. Results: The mean mHHS was 29 before surgery and 88.8 after surgery, and this increase was statistically significant (P<0.001). Good or very good clinical outcomes were achieved in 83.8% of hips. Radiological examination showed preserved stability in the vast majority of femoral and acetabular components. Acetabular component migration was detected in 2 (3.5%) hips, and femoral component migration in 2 (3.5%) hips. Activity-related thigh pain was reported in 10 hips (17.8%). Intraoperative femoral fractures occurred in 6 hips (10.7%). HO was detected in 13 hips (23.2%), mostly Brooker grade I–II. Dislocation, deep infection, and deep vein thrombosis each occurred in 1 hip (1.78%). Conclusion: Cementless THA is a reliable surgical method that yields successful early clinical and radiological outcomes when applied with appropriate patient selection and correct surgical technique. Larger series and longer follow-up are required to evaluate long-term outcomes.